FIRST EVIDENCE OF PALAEO-TETHYAN UPPER TRIASSIC CALCAREOUS NANNOFOSSILS IN NORTH DOBROGEAN OROGEN (ROMANIA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
This study presents the analysis of Upper Triassic sediments from five locations in North Dobrogea(Romania) and the Black Sea. Microfacies analyses on thin sections from the Frecăţei log reveal a shallowing trend and likely an increase in energy upward into the section. The oldest part of the log is characterised by deposition of mudstones transitioning to wackestones, with an increase of bivalves. Similar wackestones are observed in the Izvoarele and Rândunica logs, i.e. microfacies with abundant bivalves, some foraminifera and echinoderms. The offshore boreholes 816 and 817 Lebăda Vest (core CM 9 and CM 31) seem to have been deposited in a basinal or distal marine shelf environment indicated by the presence of mudstones with rare bioclasts. In contrast, sample CM 10 from borehole 816 LV is a micritised grainstone suggesting a deposition in a shallower, higher energy environment.Scanning electron microscope observations reveal a moderate diagenetic alteration in all studied samples, mainly due to dissolution. Two calcareous nannofossil species: Prinsiosphaera triassica triassica and Eoconusphaera zlambachensis were commonly observed in sample F of the Frecăţei log, allowing for assignment of the sediments to the Rhaetian age. Two coccoliths were also observed in sample F of Frecăţei log and sample CM 9 of the borehole 816 LV indicating the presence of coccolithophorids within the study region. This discovery constitutes the first confirmed record of well-preserved, determinable Upper Triassic calcareous nannofossils in the Palaeo-Tethys Ocean.
Keywords: Prinsiosphaera triassica; Eoconusphaera zlambachensis; Rhaetian; Frecăţei; Borehole 816 LV; Black Sea; Palaeo-Tethys.